The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ssmph.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in living arrangements and mortality among older people in China

Abstract: Living arrangements in later life are dynamic, with changes associated with life events such as widowhood or moves into an institution. Previous research has found particular changes in living arrangements to be associated with an elevated risk of mortality. However, research in this area within the context of China is limited, despite China being home to the world's largest population of older people. This study investigates the impact of changes in living arrangements on older persons’ survival using the Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
(65 reference statements)
2
31
0
Order By: Relevance
“…The mechanisms by which mortality risks are associated with LA in old age are still not well known, and the findings contain some contradictions. This is partly because it is difficult to identify causal links between LA and mortality risk, as LAs in old age are quite dynamic (Feng et al 2017). For example, the presence of the spouse or partner, who is the closest and most available caregiver, supports survival and reduces the need for formal care, such as entry into a nursing home (Chappell 1991;Antonucci and Ajrouch 2007;Freedman, Cornman, and Carr 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which mortality risks are associated with LA in old age are still not well known, and the findings contain some contradictions. This is partly because it is difficult to identify causal links between LA and mortality risk, as LAs in old age are quite dynamic (Feng et al 2017). For example, the presence of the spouse or partner, who is the closest and most available caregiver, supports survival and reduces the need for formal care, such as entry into a nursing home (Chappell 1991;Antonucci and Ajrouch 2007;Freedman, Cornman, and Carr 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of cross-sectional studies and a few longitudinal studies conducted in China have indicated that living arrangements have an effect on mortality [ 18 , 13 ], functional disability [ 19 ], cognitive impairment [ 20 ], psychological health [ 21 23 ], and self-rated health [ 24 ] of the old-age adults. Health-Related Quality of Life ( HRQOL), which was defined as an individual’s or a group's perceived physical and mental health over time by the Center for Disease Control and Prevention (CDC) recently[ 25 ], has also been investigated as an important overall health outcome for the elderly with different living arrangements [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as Bromell and Cagney (2014) stated, living environments may provide varied opportunities for social integration, companionship, and engagement with others. Within the current study, living in a private home was related to better social sup port, which indicates that people living at home may have close family or friends nearby to maintain close connections, which is consistent with past studies (Ashida & Heaney, 2008;Feng et al, 2017). Ewen et al…”
Section: Group Differences In Social Resources Activities Of Daily Lsupporting
confidence: 92%
“…Connidis and Davies (1992) posited that spouses and friends act as the primary companionships for older adults, and Bromell and Cagney (2014) identified the importance of receiving that companionship tied to the specific living arrangement in an older adult's life. Feng, Falkingham, Liu, and Vlachantoni (2017) underlined the importance of receiving social support in varying living environments for older adults. Ashida and Heaney (2008) (Ewen, Washington, Emerson, Carswell, & Smith;Paganini-Hill, 2013;Sarwari, Fredman, Langenberg, & Magaziner, 1998).…”
Section: Hypothesized Modelmentioning
confidence: 99%